PENGARUH KERAMAHAN KARYAWAN, PEMAHAMAN TENTANG PRODUK, DAN KERAGAMAN ITEM PRODUK TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN PADA ALFAMART DI WILAYAH KOTA SURABAYA - Retna Anggitaningsih (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2023)
This study aims to explain the effect of employee friendliness, understanding of the products sold, and the diversity of product items on consumer loyalty through consumer satisfaction at Alfamart in the city of Surabaya. The object of observation is consumers who visit Alfamart to shop. In this study, observations were made of 200 consumers who were shopping at Alfamart stores, provided that the consumer has made purchases at least five times at any Alfamart store in Surabaya. The analytical method used is the structural equation model (SEM), with exogenous variables: friendliness of salespeople; the salesperson's understanding of the products, and the completeness and variety of available product items; endogenous variables: consumer loyalty; and the intervening variable: consumer satisfaction. The compared models are model-1, where loyalty is positioned as an endogenous variable with customer satisfaction as an intervening variable, and model-2, where customer satisfaction is an endogenous variable with loyalty as an intervening variable. The findings and results of the study indicate that: (1) the friendliness of the salesperson has a significant positive effect on customer satisfaction; (2) customer satisfaction has a significant positive effect on loyalty; and (3) from the comparison of the two models, it can be stated that the better model in explaining the phenomenon under study is model-1. Thus, these findings further support the theory that loyalty arises after a person feels satisfied.